The New Zealand Home Front during World War One and World War Two - Parsons, Gwen (History compass, 2013)
During both the First World War and the Second World War, New Zealand despatched large Expeditionary Forces to assist in Britain's war effort. The home front experience was markedly different during each war. The defining characteristics of the home front during the Great War were the voluntary nature of patriotic participation and the remoteness of the war. In contrast, during the Second World War, the front was much closer to New Zealand, and the pressures of this much larger-scale conflict meant that the government was forced to exert much more control over the civilian community. The historiography of the New Zealand home front reflects these characteristics. The historiography of the Great War home front, where day-to-day life continued with a large degree of continuity, is very limited. In contrast, much attention has been paid to life on the home front during the Second World War, as the civilian population was directed into war work as well as military service.